Hubungan Antara Komunikasi Interpersonal Orang Tua Dengan Perilaku Bullying Pada Remaja - Sulistyorini, Henny; , Dra. Partini, M.Si (2016)
Adolescence is the period of life which is full of dynamic, since the development stage in this period change very rapidly. This period is in a transition step and adolescents are at high risk of experiencing delinquency and violence, either as victims or the people who conduct the violence activity which then lead to bullying behavior. One of the factors that influence the bullying behavior is the interpersonal communication of parent. The purpose of this study was to determine the negative relationship of parent interpersonal communication on bullying behavior of adolescents. The hypothesis proposed for this study was there is a negative relationship of parent interpersonal communication on bullying behaviors. This study was done by using quantitative methods. The subject of this study was the VIII grade students of junior high school, 91 students. The sampling technique of this study was done by using a quota sampling technique in accordance with the number of subjects determined by researchers and selected by the classroom teacher. The data collection method was done by using bullying behavior scale, and parents interpersonal communication analytical methods performed by using product moment analysis technique of SPSS (Statistical Product and Service Solution) 16.0 for Windows Program. Based on the analysis of the study obtained r value - 0.667; p = 0.000 (p <0.01), there is a negative relationship of parent interpersonal communication on bullying behavior. Bullying behavior has a low categorization with an empirical mean (EM) = 39.52 and hypothetical mean (HM) = 52.2, and parents interpersonal communication has a high categorization with an empirical mean (EM) = 46.84 and hypothetical mean (HM) = 40. Thw effective contribution of parents interpersonal communication variables on bullying behavior is 44.5%, the remaining of 55.5% are other factors that influence the bullying behavior.